Dog days - Franceschini, Ivan 1983-; Loubere, Nicholas (Made in China yearbook, 2019)
According to the Chinese zodiac, 2018 was the year of the 'earthly dog'. In the middle of the long, hot, and feverish dog days of the summer of 2018, some workers at Shenzhen Jasic Technology took their chances and attempted to form an independent union. While this action was met by the harshest repression, it also led to extraordinary demonstrations of solidarity from small groups of radical students from all over the country, which in turn were immediately and severely suppressed. China's year of the dog was also imbued with the spirit of another canine, Cerberus--the three-headed hound of Hades--with the ravenous advance of the surveillance state and the increasing securitisation of Chinese society, starting from the northwestern region of Xinjiang. This Yearbook traces these latest developments in Chinese society through a collection of 50 original essays on labour, civil society, and human rights in China and beyond, penned by leading scholars and practitioners from around the world